Odpowiedzi

2009-10-06T16:51:28+02:00
2 1/13 * (1,5 + 2 ⅚) : (2,4 - 1 ⅘) = 27/13 * 4⅓ : ⅗ = 27/13 * 13/3 : ⅗ = 9 : ⅗ = 15
(w dzieleniu mnożymy odwrotność 2. liczby)
6% z 15 = 0,06 * 15 = 0,9

(30 - 19⅕) : 0,3 = 10,8 : 0,3 = 36
40% z 36 = 40% * 36 = 14⅖
7 4 7
Najlepsza Odpowiedź!
2009-10-06T17:12:24+02:00
2 1/13 * (1,5 + 2 ⅚) : (2,4 - 1 ⅘) =
=21/13*(1 i3/6+2 i5/6):(2 i 4/10 -1 i 8/10)=
=21/13*3 i 8/6:2i6/10=
= 27/13 * 4⅓ : ⅗ =
=27/13 * 13/3 : ⅗ =
= 9 : ⅗ =
=15

6% z 15 = 6/100 * 15 = 0,9

(30 - 19⅕) : 0,3 =
= 10,8 : 0,3 =
= 36
40% z 36 = 40/100* 36 =
=14⅖
6 3 6
2009-10-06T17:47:26+02:00
2 1/13 * (1,5 + 2 ⅚) : (2,4 - 1 ⅘) = 27/13 * 4⅓ : ⅗ = 27/13 * 13/3 : ⅗ = 9 : ⅗ = 15
(w dzieleniu mnożymy odwrotność 2. liczby)
6% z 15 = 0,06 * 15 = 0,9

(30 - 19⅕) : 0,3 = 10,8 : 0,3 = 36
40% z 36 = 40% * 36 = 14⅖
1 1 1